Stabilizing China's Housing Market - Koss, Richard; Shi, Xinrui (Washington, D.C. : International Monetary Fund, 2018)
The sharp rise of house prices in China's Tier-1 cities has fostered a great deal of commentary about the possibility of bubbles forming there. However, China's unique housing market characteristics make it difficult to assess the macroeconomic severity of bursting bubbles, even if they exist. These include the setting of land supply and prices by the government, among many others. The presence of overbuilt 'ghost cities' greatly complicates the ability of traditional macroeconomic policies to address these concerns. This paper looks at proposals to shore up the mortgage underwriting and legal infrastructure to help China withstand the impact of falling prices, should this occur.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet